Hear and Touch, Shamsabad: Understanding creative expression through sensory stimuli (Le Topical, 2016)
A collaboration of partially sighted and blind children with art and design educators. Led by Rabeya Jalil, Beenish Khalid. Project synopsis translated in Braille
English
Keywords: Braille; Children; N7560-8266 Visual Arts. Special subjects of art; Sensory stimulus